U?UL FIQH ‘INDAL MA?HAB AL-IM?M AHMAD BIN HAMBAL WA A?ARUHU F? AL-QA??YA AL-?MMAH AL-ISL?M?YAH - Putra, Dedisyah; Nasution, Liantha Adam (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
The views of some people who state that Imam Ahmad bin Hambal is not known as a fiqh expert. He was better known as a hadith expert in his time. Wrestle around the science of hadith and explore this field. In the science of hadith, there is no known qiyas and ijma 'as contained in the science of ushul fiqh. In the study of the science of hadith, the truth is very clear and vice versa. Consideration of benefits and harms tends to be more frightening when compared to a problem understood by the system that applies in the science of ushul fiqh. This research is a qualitative literature review that discusses the position of Imam Ahmad bin Hambal and his followers in the spread of the knowledge of ushul fiqh. As a result of this research, it can be concluded that Imam Ahmad bin Hambal has a real contribution to the spread of the science of ushul fiqh and its application in the lives of Muslims. This is at least marked by the number of Imam Ahmad bin Hambal's teachers who are experts in the science of ushul fiqh as well as his students who care and practice ushuliyah rules to answer religious problems that occur in the community. Their work has contributed to the life of Muslims as a rebuttal to the assumption by some people that Imam Ahmad bin Hambal or the Slavi school is very minimal in the study of ushul fiqh so that it tends to be more extreme compared to other schools of thought. In fact, if we are honest, then we will find that the Slavi school has a major contribution to the development of the science of ushul fiqh even though in legal fatwas it is still more likely to interpret an issue of Islamic law through the approach of hadith fiqh. Keywords: Usul Fiqh, Imam Ahmad bin Hambal, Islamic Law